Settling the Frontier : Land, Law and Society in the Peshawar Valley 1500-1900 - Nichols, Robert (Karachi Oxford University Press, 2001)
A political and social history of the Peshawar region in the period 1500-1900. The text examines how the region's residents experienced imperial expansion, technological innovation and the growth of state institutions, yet maintained indigenous power relations and socio-cultural practices
Include Appendix, Glossary, Bibliography and Index
Keywords: Pushtuns -- Pakistan--Peshawar Region -- Pushtuns -- Pakistan -- Peshawar Region -- History